GAMBARAN NYERI PADA PASIEN DENGAN NEUROPATI DIABETIK YANG DIRAWAT DI RUANG PERAWATAN MEDIKAL BEDAH - Llaksono, Eko Budi; Sucipto, Ade (Jurnal Kesehatan Karya Husada, 2025)
ABSTRACT Neuropathic pain is a common complication in patients with diabetes mellitus due to peripheral nerve damage. This type of pain is chronic, disrupts comfort, and may decrease the patient's quality of life. This study aims to describe the intensity and characteristics of pain in patients with diabetic neuropathy hospitalized in the medical-surgical ward. This research used a descriptive design with a quantitative approach. A total of 30 respondents were selected using purposive sampling technique. The instruments used were a numerical rating scale to assess pain intensity and the Douleur Neuropathique 4 (DN4) questionnaire to identify neuropathic pain characteristics. The results showed that most patients experienced moderate pain (46.7%), mild pain (33.3%), and severe pain (20.0%). The most dominant pain characteristics were burning sensations (73.3%), tingling (63.3%), and stabbing pain (53.3%). As many as 80.0% of respondents had a DN4 score ≥ 4, indicating the presence of neuropathic pain. These findings highlight the importance of comprehensive pain assessment in patients with diabetes mellitus to provide appropriate management and improve the quality of nursing care.